2021
DOI: 10.1111/crj.13361
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of noninvasive ventilation in COVID‐19 related‐acute respiratory distress syndrome

Abstract: Introduction: During this long COVID-19 pandemic outbreak, continuous positive airway pressure (CPAP) and noninvasive ventilation (NIV) are being widely used to treat patients with moderate to severe acute respiratory failure (ARF). As for now, data on the efficacy of NIV in COVID-19 acute respiratory distress syndrome (ARDS) are lacking, and for this reason it is extremely important to accurately determine the outcomes of this strategy. This study aimed to evaluate clinical data and outcomes of NIV in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
2
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 16 publications
(32 reference statements)
4
68
2
3
Order By: Relevance
“…Recently, Ward-COVID, a multicentre study from 31 hospitals in Italy successfully applied CPAP/NIV in 909 patients (10.4% of all patients with respiratory failure) in a ward with an NIV failure rate 37.6% [ 47 ]. There are plenty of other studies from different countries describing successful application of CPAP [ 42 , 46 , 48 , 49 , 50 ] or NIV [ 41 , 51 , 52 ] in a ward, with the vast majority of patients receiving CPAP support. However, the experience of staff in the use of these modalities, the nurse/patient ratio and the intensity of the monitoring probably are not similar in all studies.…”
Section: Noninvasive Ventilation In Covid-19-associated Respiratory Failure: Practical Aspectsmentioning
confidence: 99%
“…Recently, Ward-COVID, a multicentre study from 31 hospitals in Italy successfully applied CPAP/NIV in 909 patients (10.4% of all patients with respiratory failure) in a ward with an NIV failure rate 37.6% [ 47 ]. There are plenty of other studies from different countries describing successful application of CPAP [ 42 , 46 , 48 , 49 , 50 ] or NIV [ 41 , 51 , 52 ] in a ward, with the vast majority of patients receiving CPAP support. However, the experience of staff in the use of these modalities, the nurse/patient ratio and the intensity of the monitoring probably are not similar in all studies.…”
Section: Noninvasive Ventilation In Covid-19-associated Respiratory Failure: Practical Aspectsmentioning
confidence: 99%
“…24 Specific NIV studies in COVID-19 largely focused on the use of CPAP in the non-ICU setting (Table 3). [183][184][185][186][187][188][189][190][191][192][193][194][195][196] Unfortunately 46% of these were research letters often lacking pertinent data. [183][184][185][186][187][188] Nonetheless, 71% of all studies reported relatively low failure rates of 11-28%; and relatively low associated mortality among those without care limitations (< 30%).…”
Section: Lung Recruitment Potentialmentioning
confidence: 99%
“…185,188,196 In 8 traditional observational studies, failure rates were 17-57% with associated mortality of 22-97%. [189][190][191][192][193][194][195][196] In some studies substantially higher mortality was reported in subjects in which the pre-NIV P aO2 /F IO2 was < 150 mmHg (53%), 189 or had care limitations in place (55-72%). 187,190,195 NIV duration was reported in 50% of studies with median values of 5-6 days.…”
Section: Lung Recruitment Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this context, CPAP is a much less resource intensive option than IMV and was trialled for CARDS patients in Italy early in the pandemic with promising results(8). Studies conducted in various settings since then have produced mixed results on the effectiveness of CPAP in CARDS compared with IMV(915), but CPAP still retains its place in prominent guidelines(16,17). However, studies from resource limited settings, which now account for the majority of new Covid19 cases(18) and deaths have been limited.…”
Section: Introductionmentioning
confidence: 99%